The trend of sharenting among Malaysian parents: a qualitative study on their content and motivation - Lee Jia Wen; Crendy Tan; Saroja Dhanapal (International Journal of Public Health Science (IJPHS), 2022)
With social media having penetrated people’s daily life, sharenting has become a common phenomenon among the current generation. The term “sharenting” is derived from the combination of the words “share” and "parenting” which refers to parents who often post or share their children’s photos/videos on social media such as Facebook, Instagram, Snapchat, YouTube, Blog, and so on. Sharenting has resulted in a lot of consequences due to the sharing of children’s information. To understand the consequences of sharenting, the current research analysed the contents of children’s information that are shared by parents in Malaysia. The research also investigated the reasons that motivated parents to be involved in the trend of sharenting. A qualitative research adopting one-to-one interview was conducted to obtain in-depth information and knowledge from the respondents selected through a non-probability snowball sampling method. The responses from the interviews were analysed using a thematic analysis where it was noted that in terms of the content shared, two key themes emerged specifically funny and interesting photos as well as children’s educational progress. On the other hand, in terms of reasons for sharenting, the respondents listed several reasons including to keep in touch with friends/family members, to keep as memories, and gain support from others.